Resilient Cities Report 2015. Global developments in urban adaptation and resilience. Based on the Proceedings of the 6th Global Forum on Urban Resilience and Adaptation 8 - 10 June 2015 Bonn, Germany. - Mitroliou, Evgenia; Kavanaugh, Laura (My University, 2015)
Resilient Cities is the global forum on urban resilience and adaptation convened in Bonn, Germany. The congress series provides an international platform to share the latest information, good practices, challenges, and innovations for creating more resilient cities. The outcomes present an annual snapshot of the state of urban resilience, building on discussions and developments from previous years. In 2015, the 6th edition of Resilient Cities focused on practical application and implementation, with a prominent track dedicated to financing resilience. Through concrete examples, participants gained insight into topics such as resilient infrastructure, city data and indicators, disaster risk reduction, resilient urban food systems and collaborative approaches. Emergent topics including communicating resilience and resilient public health systems were also discussed. The importance of inclusive urban development and the informal sector were cross-cutting issues which will be further explored at Resilient Cities 2016. This report aims to reflect the outcomes of Resilient Cities 2015 and broader activities in the field of urban resilience and climate change adaptation. Based on the expertise of international experts and practitioners, the following pages present case studies and lessons learned from around the world, as well as challenges and gaps. The text is best understood in conjunction with the 2013 and 2014 Resilient Cities Congress Reports.
Keywords: Stadtentwicklungsplanung; Indikator; Bewertung; Finanzierung; Ernährung; Gesundheitswesen; Kommunikation; Nachhaltigkeit; Nachhaltigkeitsindikator; Nachhaltige Entwicklung; Resilienz; Empfehlung